Associations between antimony exposure and glycated hemoglobin levels in adolescents aged 12-19 years: results from the NHANES 2013-2016 - Baoying Feng; Baoying Feng; Baoying Feng; Peng Tang; Sheng He; Sheng He; Sheng He; Sheng He; Zhenren Peng; Zhenren Peng; Zhenren Peng; Zhenren Peng; et al. (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to investigate the association between antimony (Sb) exposure and glycated hemoglobin (HbA1c) levels in adolescents.MethodsA cross-sectional study of 751 adolescents aged 12-19 years was conducted via the National Health and Nutrition Examination Survey (NHANES, 2013-2016). Survey-weighted linear regression and restricted cubic spline (RCS) analyses were applied to evaluate the relationship of urinary Sb exposure with HbA1c.ResultsA significant relationship was observed between urinary Sb concentrations and HbA1c levels (percent change: 0.93; 95% CI: 0.42, 1.45) after full adjustment. After converting urinary Sb levels to a categorical variable by tertiles (T1-T3), the highest quantile was associated with a significant increase in HbA1c (percent change: 1.45; 95% CI: 0.38, 2.53) compared to T1. The RCS models showed a monotonically increasing relationship of urinary Sb with HbA1c. Subgroup analyses revealed a sex-specific relationship between urinary Sb exposure and HbA1c with a significant positive association in males and a non-significant positive association in females. Sensitivity analyses further confirmed the relationship between urinary Sb and HbA1c, even after excluding participants who were overweight or obese (percent change: 1.58%, 95% CI: 0.88, 2.28) and those with serum cotinine levels ≥ 1 ng/mL (percent change: 1.14%, 95% CI: 0.49, 1.80).ConclusionOur findings indicated that increased Sb exposure may correlate with higher HbA1c levels, especially in male adolescents. More studies are needed to further explore and validate the potential mechanisms.